2022
DOI: 10.3390/su15010409
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Underlying Causes of Waste Generation in Indonesia’s Construction Industry

Abstract: The construction industry produces enormous volumes of construction waste that have a negative influence on the environment. This study examines the underlying causes of waste generation in the Indonesian construction industry based on professional perspectives. This study used a questionnaire as a research instrument and examined the data with reliability and exploratory factor analysis. Based on the analysis, there are eight underlying causes that contribute to the generation of construction waste in the Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…On the one hand, higher labor efficiency indicates that construction workers in the area are more experienced and competent, and they will pay greater attention to the use and loss of materials in the construction process in order to prevent unnecessary wastage (Karunasena et al, 2023). Labor efficiency, on the other hand, is also responsive to the level of management of the building construction process, and a scientifically sound and reasonable management process can significantly reduce construction waste generation (Fitriani et al, 2022).…”
Section: Technological Factormentioning
confidence: 99%
“…On the one hand, higher labor efficiency indicates that construction workers in the area are more experienced and competent, and they will pay greater attention to the use and loss of materials in the construction process in order to prevent unnecessary wastage (Karunasena et al, 2023). Labor efficiency, on the other hand, is also responsive to the level of management of the building construction process, and a scientifically sound and reasonable management process can significantly reduce construction waste generation (Fitriani et al, 2022).…”
Section: Technological Factormentioning
confidence: 99%
“…It has been confirmed that WCFs related to design and pre-contract stage (F4) have devastating effects on the WG where an inappropriate design results in up to 33% of the CW (Chellappa et al, 2023) and adoption of sustainable design mainly prefabrication could enable 52-84.7% cut of the CW (Fitriani et al, 2023) and almost 100% recovery of the demolition waste (Begum et al, 2009). Eze et al (2022) reported that 96.88% of F3-related WCFs are equally sources of cost overrun.…”
Section: Taxonomy and Discussionmentioning
confidence: 99%
“…Likewise, procurement and onsite construction stages are highly contributing to the CW and are influenced by transversal WCFs families. Fitriani et al (2023) showed that 25.96%, 19.96%, 14.25%, and 11.59% of CWs could be explained by improper management of equipment, onsite material logistics, and working milieu (F6); onsite-related inadequate collaboration and communication on the construction site (F3); improper site planning and workforce management (F6), and F1 due to involved stakeholders in the construction operation (waste behavior, incompetency, and lack of training and experience), respectively. Based on risk severity and occurrence analyses, Bachayo et al (2022) revealed that among 8 WCFs related to procurement and supply chain, 7 fell in the red zone with orders variation as the most occurrent, incompliant materials with specifications as the severest, and mistakes in quantity surveys as the most impactful on the cost.…”
Section: Taxonomy and Discussionmentioning
confidence: 99%
See 2 more Smart Citations